GC‐MS analysis of Amaryllidaceae and Sceletium‐type alkaloids in bioactive fractions from Narcissus cv. Hawera. (25th May 2021) - Berkov, Strahil; Pechlivanova, Daniela; Denev, Rumen; Nikolova, Milena; Georgieva, Liliya; Sidjimova, Borjana; Bakalov, Dimitar; Tafradjiiska, Radka; Stoynev, Alexander; Momekov, Georgi; Bastida, Jaume
Abstract : Rationale: Narcissus cv. Hawera has been found to biosynthesize some Sceletium ‐type alkaloids with antidepressant and anxiolytic activities. This ornamental plant has been poorly studied as a source of bioactive alkaloids including some contraversive reports on in vitro and intact plants. In this study, a detailed GC‐MS characterization of its alkaloid fractions is presented. Methods: GC‐MS was used for the identification of compounds in the alkaloid fractions. Both underivatized and silylated samples were analyzed simultaneously. Elevated plus maze and tail suspension tests were used to assay the anxiolytic and antidepressant activities. Ellman's and MTT‐dye reduction assays were used to evaluate the acetylcholinesterase (AChE) inhibitory and cytotoxicity activities, respectively. Results: Of the 29 alkaloids, 13 of Sceletium ‐type were detected. Two new alkaloids were identified as 2‐oxo‐mesembrine and 2‐oxo‐ epi ‐mesembrenol. Lycorine was found as a major compound (43.5%) in the crude silylated methanol extract. After the elimination of lycorine by pre‐crystallization, the major alkaloids were 40.8% 6‐ epi ‐mesembranol, 16.2% 6‐ epi ‐mesembrenol, and 13.8% sanguinine. This fraction showed anxiolytic and antidepressant‐like activities as well as potent AChE inhibitory and antineoplastic activities. Conclusions: Silylation of the alkaloid fractions from Narcissus cv. Hawera provides better separation, structural information, and improved sensitivity for compounds with two and more hydroxyl groups. The lycorine‐free alkaloid fraction shows a great potential for further pharmacological studies.